Location, Location, Locution: Why it Matters Where We Say What We Say - Ruitenberg, Claudia W. (Philosophical Inquiry in Education, 2017)
This paper addresses educators’ responsibility for the discourse (including their own and others’) that circulates in educational settings. This issue tends to arise especially with hurtful language and other discursive acts that have negative effects, and that require an apology, correction, or some other kind of remedial discourse. The paper frames this “discursive responsibility” as particularly contingent on location, arguing that when educators address their own or others’ discourse, the response needs to be at a level of publicity that is the same as, or as similar as possible to, the discursive act it responds to.